Effect of host plants on nutritional performance of cotton bollworm, Helicoverpa armigera (Lepidoptera: Noctuidae) - Abdelhammid Gacemi; Ahmed Taibi; Djamal Bellague; Kheirddin Tarmoul (Journal of Crop Protection, 2022)
In this study, the nutritional indices of the larval stages of Helicoverpa armigera were determined on four vegetable crops under laboratory conditions (25 ± 1 °C, 65 ± 5% RH, with a 16:8 (L: D) h photoperiod). The third instar larvae reared on potato showed the highest value of efficiency on the conversion of ingested food (ECI) and efficiency of conversion of digested food (ECD) (8.281 ± 0.767% and 11.016 ± 1.142%, respectively). The highest (0.129 ± 0.014 mg/mg/day) and lowest (0.069 ±0.012 mg/mg/day) relative growth rate (RGR) of the fourth instar larvae were obtained on potato and tomato, respectively. Data indicated that the highest value of (ECI) and (ECD) for fourth instar larvae were on tomato (12.361 ± 2.258% and 18.588 ± 3.834%, respectively). The lowest value of the relative consumption rate (RCR) and approximate digestibility (AD) of the fifth instar was recorded on tomato (0.592 ± 0.063 mg/mg/day) and potato (51.85 ± 4.607%), respectively. The ECI and ECD values of the fifth larval instar were the highest on tomato (12.477 ± 1.333% and 17.624 ± 1.609%, respectively). Overall, among different host plants tested, the highest ECI and ECD of all the larval instars were observed on tomato (9.813 ± 0.692% and 12.506 ± 0.882%, respectively), and the lowest values (3.735 ± 0.201% and 5.463 ± 0.426%) were on artichoke. Tomato and artichoke were the most nutritionally suitable and unsuitable host plants, respectively, for H. armigera.